KAJIAN TAFSIR ASY-SYARAWI: KARAKTER GURU DALAM MENDIDIK PESERTA DIDIK DALAM SURAH LUQMAN AYAT 13 - Efendi, Ruslan; Mas Suwita, Ade; Krisnadi, Krisnadi (Jurnal Bilqolam Pendidikan Islam, 2023)
This paper raises the question how should the teacher's character be in educating students. Good education begins with a teacher who is correct in educating his students. This paper aims that teachers as educators know how to educate students through the explanations contained in the Al-Quran surah Luqman verse 13, using the Library Research method with a content analysis approach to provide a real picture for analyzing content with Asy-Syarawi Tafsir. The results of the study show that Asy-Syarawi's interpretation in surah Luqman verse 13 provides an explanation that it is better if the teacher educates students with affectionate calls, then education cannot be separated from the teachings of the Al-Quran which are interrelated and cannot be separated both to form and prepare students who obey the teachings of Shari'a by not associating partners with Allah. So that students are formed who are in line with the goals of Islamic education.